659 AN SINGLE-ARM OPEN-LABEL PHASE II STUDY OF CAMRELIZUMAB PLUS APATINIB AS SECOND-LINE TREATMENT FOR ADVANCED ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (17th September 2021) - Wang, Feng; Fan, Qingxia; Wang, Junsheng; Wu, Tao; Hong, Yonggui; Meng, Xiangrui; Ren, Zhonghai; Guo, Yanzhen; Yang, Xiuli; Shi, Pei; Yang, Jiamei; Yin, Xianzhe; et al.
Abstract:  : Esophageal squamous cell carcinoma (ESCC) as a common malignancy is prevalent in East Asia and in eastern and southern Africa. Although pembrolizumab, nivolumab and camrelizumab are respectively recommended as second-line treatment for advanced ESCC due to improved overall survival (OS), objective response rate (ORR) was modest. New effective treatments are needed. Hence, the study of camrelizumab plus apatinib (VEGFR2 inhibitor) as second-line treatment for advanced ESCC was performed. Methods: This ongoing phase II trial (NCT03736863) in six sites in China enrolled pts aged 18-75 with unresectable locally advanced, locally recurrent, or metastatic ESCC that progressed or were intolerant after first-line chemotherapy, and an ECOG performance status of 0-1. Pts received 200 mg camrelizumab intravenously every 2 weeks and apatinib 250 mg orally once per day in 4-week cycles until disease progression, unacceptable adverse events (AEs) or withdrawal of consent. The primary endpoint was investigator-assessed ORR. Secondary endpoints included disease control rate (DCR), progression-free survival (PFS) and OS. Results: At data cutoff (Feb 28, 2021), 52 pts were enrolled, including 42 males and 50 with distant metastases, with the median age of 62 years. In the evaluable population of 39 pts, ORR without confirmation was 43.59% and DCR was 94.87%. The median duration of response was 6.9 months (95% CI 4.57–9.23). The median PFS was 6.8 month (95% CI 2.66–10.94). The 12-month overall survival was 52.2%. A total of 80.8% of pts had treatment-related AEs (TRAEs) with 46.2% of grade ≥ 3 TRAEs. The safety profile of camrelizumab and apatinib was consistent with other anti–PD-1 antibodies and angiogenesis inhibitors. Conclusion: This is the first study that evaluates the combination anti–PD-1 antibody and anti-angiogenesis inhibitor as a second-line therapy for advanced ESCC. Camrelizumab plus apatinib showed encouraging clinical efficacy and acceptable safety. Further phase III randomized trials are warranted.